The Influence of the Quality of Learning Communication Media on Students Interest in Learning: The case at Mamba'ul Ulum Islamic Boarding School Vocational School, Sindang Jawa, Cirebon - Yusuf Sapari; Rizki Budhi Suhara (Faculty of Ushuluddin and Dakwah, UIN K.H. Abdurrahman Wahid Pekalongan, Central Java, Indonesia, 2023)
The importance of an education is to increase the nation's competitiveness which aims to create social justice. Shows that Indonesia must continue to spur investment in human resources. On this it can be said that education has relevanto investment in human resources. The priority scale in our current education is vocational education. Both the upper secondary level (SMK) and tertiary education such as poly,technics, D3 and D4 Communication in the field of education is a very important element and has a very large role in determining the success of education. The teaching and learning process carried out in the classroom mostly occurs due to communication in the field of education. Thus it can be stated that educational communication can be interpreted as instructional communication. In this study, the population was the students of the Manbaul Ulum Dukuntang Vocational High School, the competence of Visual Communication Design skills. While the sample is DKV Class XI and XII students at the Mamba'ul Ulum Islamic Boarding School. Testing techniques using validity test, reliability test and regression test. Based on statistical tests that measure the effect of the quality of learning media on learning interest, the results show that all of them meet the requirements for carrying out the regression test. The results obtained on the quality of learning communication media in productive lessons in the field of Visual Communication Design expertise which consists of four dimensions, including Material, Presentation Order, Language and Attraction get a value of 4.09 on a scale of 1-5 which means good. The learning interest of students who take part in learning productive subjects by using learning communication media which consists of four dimensions, including Likes, Interest, Attention and Involvement get a score of 3.89 on a scale of 1-5 which means good, the regression test is 0.398 which indicates that the quality learning communication media has an effect of 39.8% on student learning interest.